Promotion of innovation and Job Growth in Small- and Medium-Sized Enterprises in Australia: Evidence and Policy Issues - Bloch, Harry; Bhattacharya, M. (Wiley-Blackwell Publishing Asia, 2016)
Small- and medium-sized enterprises play a substantial role in Australian growth and job creation. We discuss approaches to understanding the drivers of innovation and review evidence on the determinants of innovation by Australian small- and medium-sized enterprises. We also examine the role of these firms in job creation. Against this evidence and the conceptual underpinnings, we then discuss some issues that arise with the government's current innovation agenda.